Program Pemberdayaan untuk Membangun Ketahanan Keluarga Bagi PMI Pasca Pemulangan Ke Indonesia: Sebuah Tinjauan Singkat - Tresia Lemauk; Maria Puspitasari (Journal on Education, 2023)
Indonesian Migrant Workers as foreign exchange earners for the country, often face problems both when leaving and working in destination countries, and after returning home. The problems faced are often related to resilience in terms of family life, or family resilience. One of the steps taken by BP2MI to help build family resilience is through program empowerment. Departing from this situation, research is directed at identifying empowerment programs using the concept of human capital and community empowerment, and analyzing the concept of family resilience. The approach used is qualitative and the data collection technique is interviews conducted with migrant workers and BP2MI representatives after carrying out a document study. The results of the study show that from the people centered, participatory, sustainable aspect, there are weaknesses that arise, namely not fully involving all existing elements, which can affect sustainability in the aspect of family and community resilience. From the aspect of human capital, there are still weaknesses in individual motivation, so BP2MI needs to pay attention. And from the aspect of family resilience, in terms of independence it has not been built as seen in the very high dependency of the training participants on the institution, both in terms of capital and operational activities.